Giant Optical Anisotropy in a Covalent Molybdenum Tellurite via Oxyanion Polymerization - Tianhui Wu; Xingxing Jiang; Kaining Duanmu; Chao Wu; Zheshuai Lin; Zhipeng Huang; Mark G. Humphrey; Chi Zhang (Advanced Science, 2024)
Abstract Large birefringence is a crucial but hard‐to‐achieve optical parameter that is a necessity for birefringent crystals in practical applications involving modulation of the polarization of light in modern opto‐electronic areas. Herein, an oxyanion polymerization strategy that involves the combination of two different types of second‐order Jahn–Teller distorted units is employed to realize giant anisotropy in a covalent molybdenum tellurite. Mo(H2O)Te2O7 (MTO) exhibits a record birefringence value for an inorganic UV‐transparent oxide crystalline material of 0.528 @ 546 nm, which is also significantly larger than those of all commercial birefringent crystals. MTO has a UV absorption edge of 366 nm and displays a strong powder second‐harmonic generation response of 5.4 times that of KH2PO4. The dominant roles of the condensed polytellurite oxyanions [Te8O20]8− in combination with the [MoO6]6− polyhedra in achieving the giant birefringence in MTO are clarified by structural analysis and first‐principles calculations. The results suggest that polymerization of polarizability‐anisotropic oxyanions may unlock the promise of birefringent crystals with exceptional birefringence.